2000
DOI: 10.1046/j.1464-410x.2000.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between clinical outcome and residual prostatic weight ratio after transurethral resection of the prostate for benign prostatic hyperplasia

Abstract: Objective To assess in a prospective study the use of a new variable, the residual prostatic weight ratio (RPWR), for evaluating the clinical outcome after transurethral resection of the prostate (TURP). Patients and methods From April 1996 to June 1997, 40 men (mean age 70.4 years, range 53± 85) with symptomatic benign prostatic hyperplasia were evaluated using the American Urological Association (AUA) symptom score, measurements of the mean and maximum urinary¯ow rate (Q ave and Q max ), and by transrectal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
0
23
2
2
Order By: Relevance
“…While some authors have suggested that better clinical results after TURP may correlate with the completeness of the resection of the obstructing adenoma (9,10), others have shown that partial resection produces short-term functional results comparable to those of standard TURP (11,12). The aim of this study was to evaluate the impact of the percent of resected tissue (PRT) during TURP on the short-term clinical outcome of patients with LUTS due to BPH.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have suggested that better clinical results after TURP may correlate with the completeness of the resection of the obstructing adenoma (9,10), others have shown that partial resection produces short-term functional results comparable to those of standard TURP (11,12). The aim of this study was to evaluate the impact of the percent of resected tissue (PRT) during TURP on the short-term clinical outcome of patients with LUTS due to BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested complete resection should be performed for better result. 19,20 while others have suggested that a partial resection is adequate for short term functional results. 21,22 The recommended TURP technique consists of a complete resection of adenomatous tissue inside the surgical capsule for better result in terms of quality of life and symptom improvement.…”
mentioning
confidence: 99%
“…The majority of such studies did not pay attention to operative parameters such as the weight of residual tissue or RPWR, both of which indicate how complete an operation is. The importance of RPWR was firstly mentioned by Chen et al (9). These authors examined 40 men with symptomatic BPH and detected that the smaller the RPWR was at 16 weeks after TURP, the better was the clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Hakenberg et al analyzed the impact of residual prostatic weight (RPW) on outcomes after TURP and did not find a significant influence of this parameter on outcome (8). In their study, Chen et al detected a correlation between operative parameters and Qmax, International Prostate Symptoms Score (IPSS) and quality of life (QoL) (9) and concluded that better results were achieved when the residual prostate weight ratio (RPWR) was smaller. In the study presented herein, RPWR and RPW cutoff values that have a significant influence on an early outcome after TURP have been identified for the first time.…”
Section: Introductionmentioning
confidence: 99%